THE EFFECT OF WORKING CAPITAL TURNOVER (WCT) AND TOTAL ASSETS TURNOVER (TATO) ON RETURN ON EQUITY (ROE) AT PT. INDOFOOD SUKSES MAKMUR, TBK - Nabila, Nur Fauziah; Huda, Nurul; Muniarty, Puji (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
This study aims to determine and analyze Working Capital Turnover (WCT) and Total Asset Turnover (TATO) on Return On Equity (ROE) at PT. Indofood sukses maju, Tbk. This type of research is an associative type of research. The research instrument used in this study is a list of tables containing sales data, current assets, current liabilities, total assets, net profit and capital at PT. Indofood sukses maju Tbk, the type of data used is secondary data obtained from financial reports obtained from the website www.indofood.com. The population in this study is the financial report data of PT. Indofood sukses maju Tbk. for 30 years since it was listed on the Indonesia Stock Exchange in 1994-2024. With the sample used from 2014-2023. The sampling technique used is purposive sampling with the criteria for the most updated financial report data available for 10 consecutive years, namely from 2014-2023. The data collection technique in this study is documentation and literature study. The data analysis techniques used are classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression analysis, correlation coefficient, determination coefficient, t-test and f-test. The results of this study state that Working Capital Turnover (X1) and Total Asset Turnover (X2) have no significant effect on Return On Equity (Y) at PT. INDOFOOD SUKSES MAKMUR, tbk.